A numerical approximation of 2D coupled Burgers` equation using modified cubic trigonometric B-spline differential quadrature method - Kapoor, Mamta; Joshi, Varun (Zielona Góra: Uniwersytet Zielonogórski)
In the present paper, trigonometric B-spline DQM is applied to get the approximated solution of coupled 2D non-linear Burgers? equation. This technique, named modified cubic trigonometric B-spline DQM, has been used to obtain accurate and effective numerical approximations of the above-mentioned partial differential equation. For checking the compatibility of results, different types of test examples are discussed.
Keywords: rigonometric B-spline; differential quadrature method (DQM); coupled 2D non-linear Burgers` equation